Women Educators’ Perspectives on AI in English Language Pedagogy in Malaysia - Abd Karim, Rafidah (European Scientific Journal, ESJ, 2026)
Artificial Intelligence (AI) is rapidly reshaping higher education, offering new approaches to teaching, learning, and assessment. In English language pedagogy, AI tools enable personalised learning, provide automated feedback, and enhance student engagement. The purpose of the study is to explore women educators’ perspectives on AI integration in their English language pedagogy. Using a qualitative approach, data were collected through semi-structured interviews with 10 women educators in a selected public university. Qualitative data were analysed using the interview results in three steps: quotation, coding, and thematic analysis using Atlas.ti. version 9.0. The findings reveal that there were five themes that emerged from the thematic analysis, namely AI as an intelligent tool, personalised learning, time-saving and enhancing efficiency, ethical issues, and empowering women in ELT. The ten participants view AI as a valuable aid for enriching pedagogy, particularly in automating repetitive tasks, supporting learner autonomy, and fostering creativity in language learning. However, challenges such as limited institutional support, ethical concerns, gendered barriers, and gaps in digital literacy present significant obstacles to effective integration. The voices of these educators highlight the dual role of AI as both an enabler of innovation and a potential source of inequality when resources and training are unevenly distributed. By emphasising the experiences of women, this study contributes new insights to the underexplored intersection of AI, gender, and language education. It underscores the need for inclusive policies, sustained professional development, and participatory approaches to ensure equitable access and effective implementation of AI in higher education. The study concludes that while AI holds transformative potential for English language pedagogy, its benefits can only be realised through responsible adoption that actively promotes gender equality and institutional readiness